Open source software possibilities for Caribbean researchers - Clarke, Christopher Martin ([CCMS] [St. Augustine]TT, 2001)
Makes the case not just for more use of open source application in Caribbean research institutions but also for the use of open source development methodologies in large collaborative projects.